Hypertension and Estrogen Deficiency Augment Aneurysmal Remodeling in the Rabbit Circle of Willis in Response to Carotid Ligation. Issue 11 (21st August 2015) - Tutino, Vincent M.; Mandelbaum, Max; Takahashi, Akira; Pope, Liza C.; Siddiqui, Adnan; Kolega, John; Meng, Hui
ABSTRACT Increased cerebral blood flow has been shown to induce pathological structural changes in the Circle of Willis (CoW) in experimental models. Previously, we reported flow‐induced aneurysm‐like remodeling in the CoW secondary to flow redistribution after bilateral common carotid artery (CCA) ligation in rabbits. In the current study, we tested the hypothesis that loading rabbits with biological risk factors for vascular disease would increase flow‐induced aneurysmal remodeling in the CoW. In the same series as the previously‐reported bilateral CCA‐ligation‐alone (n = 6) and sham surgery (n = 3) groups, eight additional female rabbits (the experimental group in this study) were subjected to two risk factors for intracranial aneurysm (hypertension and estrogen deficiency) and then bilateral CCA ligation. Upon euthanasia at 6 months, vascular corrosion casts of the CoW were created and analyzed by scanning electron microscopy for morphological changes and aneurysmal damage. In rabbits with hypertension and estrogen deficiency, arterial caliber increased throughout the CoW, similar to rabbits with CCA ligation alone. However, aneurysmal remodeling (i.e., local bulging) in the CoW was significantly greater than in CCA‐ligation‐only rabbits and was more widespread, presenting in regions that did not show aneurysmal changes after CCA ligation alone. Furthermore, hypertension and estrogen deficiency caused greater increases in vessel length and tortuosity. These results suggest that hypertension and estrogen deficiency make the CoW more vulnerable to flow‐induced aneurysmal remodeling and tortuosity. We propose they do so by lowering the tolerance of vascular tissue to hemodynamic forces caused by CCA ligation, thus lowering the threshold necessary to incite vascular damage. Anat Rec, 298:1903–1910, 2015. © 2015 Wiley Periodicals, Inc.